Clinical Reproductive Medicine and Surgery A Practical Guide - Falcone, Tommaso; Hurd, William W.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Now in a completely revised and expanded third edition, including six new chapters, this user-friendly textbook offers a succinct overview of both the medical and surgical management of reproductive disorders, as well as coverage of associated imaging modalities. Included here are updated chapters on major reproductive endocrinology and infertility issues, such as polycystic ovary syndrome (PCOS), pubertal disorders, amenorrhea, menopause, management of endometriosis and fibroids (including interventional radiology), laboratory and clinical aspects of assisted reproductive technologies (ART), imaging modalities such as ultrasonography and sonohysterography, and hysteroscopic and laparoscopic techniques. New chapters include an expansion of female infertility and fertility, preimplantation diagnosis and screening, osteoporosis, and contraception and sterilization. In addition, each chapter opens with a clinical case presentation and a list of keywords relevant to the topic at hand. Residents, fellows, and new clinicians of obstetrics and gynecology interested in reproductive endocrinology and infertility will find Clinical Reproductive Medicine and Surgery: A Practical Guide a valuable and focused reference.
Hypothalamic-Pituitary-Ovarian Axis and Control of the Menstrual Cycle -- Female and Male Gametogenesis -- Normal Puberty and Pubertal Disorders -- Fertilization and Implantation -- Reproductive Imaging -- Amenorrhea -- Polycystic Ovary Syndrome -- Abnormal Uterine Bleeding -- Menopause -- OSTEOPOROSIS FOR THE FEMALE PATIENT -- Male Infertility -- Infertility -- Fertility Preservation -- Ovarian Reserve Testing -- RECURRENT EARLY PREGNANCY LOSS -- Ovulation Induction -- Assisted Reproductive Technology: Clinical Aspects -- Assisted Reproductive Technology: Laboratory Aspects -- Preimplantation Genetic Diagnosis and Genetic Screening -- Hysteroscopic Management of Intrauterine Disorders: Polypectomy, Myomectomy, Endometrial Ablation, Adhesiolysis, and Removal of Uterine Septum -- Uterine Leiomyomas -- Tubal Disease and Ectopic Pregnancy -- Endometriosis -- Contraception and Sterilization -- Surgical Techniques for Management of Anomalies of the Müllerian Ducts.
Keywords: Medicine; Gynecology; Reproductive medicine; Andrology; Medicine & Public Health; Reproductive medicine; Gynecology; Andrology